2023
DOI: 10.1038/s41598-023-31055-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of NTRK 1/2/3 fusion prevalence pan-cancer and across solid tumours

Abstract: NTRK gene fusions are rare somatic mutations found across cancer types with promising targeted therapies emerging. Healthcare systems face significant challenges in integrating these treatments, with uncertainty in prevalence and optimal testing methods to identify eligible patients. We performed a systematic review of NTRK fusion prevalence to inform efficient diagnostic screening and scale of therapeutic uptake. We searched Medline, Embase and Cochrane databases on 31/03/2021. Inclusion criteria were studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Among the adult non-NSCLC malignancies, our study has confirmed a substantial frequency of NTRK fusions in microsatellite-unstable colorectal carcinomas (12.5%). Overall, our data on the occurrence and spectrum of NTRK translocations are in good agreement with previously published studies [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Among the adult non-NSCLC malignancies, our study has confirmed a substantial frequency of NTRK fusions in microsatellite-unstable colorectal carcinomas (12.5%). Overall, our data on the occurrence and spectrum of NTRK translocations are in good agreement with previously published studies [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…NTRK fusions are typically present in a mutually exclusive manner with other oncogenic mutations and fusions ( 3 ). In this study, concurrent EGFR sensitising mutations were identified in almost a third of cases with high NTRK expression including one patient with a concurrent EGFR L858R mutation and MET amplification.…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal rearrangements of these genes cause activation and/or overexpression of TRK receptors resulting in activation of downstream oncogenic pathways, establishing NTRK as a major target for therapy ( 2 ). NTRK gene fusions have been reported across a wide range of solid tumour types as the primary oncogenic driver, however their frequency is low in more common cancers ( 3 ). Larotrectinib, a specific TRK inhibitor, and entrectinib, a multi-kinase TRK inhibitor, have been approved by the US Food and Drug Administration and European Medicines Agency as cancer agnostic drugs for patients with solid tumours harbouring a NTRK fusion.…”
Section: Introductionmentioning
confidence: 99%
“…However, NTRK1-3 rearrangements are included in the majority of multigene diagnostic panels, so their detection is supported by the rapidly increasing utilization of NGS. While the incidence of NTRK activation in commonly occurring carcinomas affecting adults falls below 1:500-1:1000, NTRK1-3 translocations are detected at frequency of about 5% in pediatric tumors, sarcomas, and salivary gland carcinomas [53,54]. NTRK1-3 fusions are particularly common in microsatellite-unstable RAS/RAF mutation-negative colorectal carcinomas, while non-colorectal tumors with MSI rarely carry gene translocations [37].…”
Section: Ntrk1-3 Rearrangementsmentioning
confidence: 99%